Limonin Isolated From Pomelo Seed Antagonizes Aβ25-35-Mediated Neuron Injury via PI3K/AKT Signaling Pathway by Regulating Cell Apoptosis - Qiu, Yuanxin; Yang, Jingxian; Ma, Lukai; Song, Mingyue; Liu, Guo (Frontiers in Nutrition, 2022)
Pomelo seed as a by-product from pomelo consumption is rich in bioactive compounds, however, a huge volume of pomelo seed was disposed as wastes, the comprehensive utilization of pomelo seed could not only generate valued-added products/ingredients, but also decrease the environmental pollution. In this study, the main active substance limonin in pomelo seed was considered as a high-value bioactive compound. The purification of limonin from pomelo seed was investigated, and the neuroprotective and mechanism were characterized. The UPLC-MS/MS results indicated that 29 compounds in pomelo seed were identified, including 14 flavonoids, 3 limonids, 9 phenols and 3 coumarins. Moreover, high purity of limonin was obtained by crystallization and preparative-HPLC. Furthermore, limonin pretreatment can antagonize the cell damage mediated by Aβ25–35 in a concentration-dependent relationship. The regulation of Bax/Bcl-2, expression of caspase-3 protein and the activation of PI3K/Akt signaling pathway were observed in the cells pretreated with limonin. Treatment of PC12 cells with PI3K inhibitor LY294002 weakened the protective effect of limonin. These results indicated that limonin prevented Aβ25–35-induced neurotoxicity by activating PI3K/Akt, and further inhibiting caspase-3 and up-regulating Bcl-2. This study enables comprehensive utilization of pomelo seed as by-product and offers a theoretical principle for a waste-to-wealth solution, such as potential health benefits of food ingredient and drug.